2008
DOI: 10.1111/j.1530-0277.2008.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Food Availability and Administration of Orexigenic and Anorectic Agents on Elevated Ethanol Drinking Associated With Drinking in the Dark Procedures

Abstract: Background-Drinking in the dark (DID) procedures have recently been developed to induce high levels of ethanol drinking in C57BL/6J mice, which result in blood ethanol concentrations reaching levels that have measurable affects on physiology and/or behavior. The present study determined if increased ethanol drinking associated with DID procedures may be motivated by caloric need rather than by the post-ingestive pharmacological effects of ethanol. To this end, food availability was manipulated or mice were giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 19 publications
4
52
2
1
Order By: Relevance
“…It seems likely that peripherally administered ghrelin will have similar effects on alcohol reward as we have previously shown that systemic ghrelin treatment also increases accumbal dopamine release, increases locomotor activity, and induces a CPP response (32). In contrast to our data for central ghrelin administration, another study did not observe a similar increase in alcohol consumption when ghrelin was administered peripherally (33). The most likely explanation for the discrepancy relates to the protocol.…”
Section: Discussioncontrasting
confidence: 55%
“…It seems likely that peripherally administered ghrelin will have similar effects on alcohol reward as we have previously shown that systemic ghrelin treatment also increases accumbal dopamine release, increases locomotor activity, and induces a CPP response (32). In contrast to our data for central ghrelin administration, another study did not observe a similar increase in alcohol consumption when ghrelin was administered peripherally (33). The most likely explanation for the discrepancy relates to the protocol.…”
Section: Discussioncontrasting
confidence: 55%
“…Mice in each group were given access to either water or ethanol (20%), respectively, on a weekly schedule that started with 2 hours (2 h) access a day for 3 days, followed by 1 day 4 hour (4 h) access session, and then 3 days of abstinence, for a total of 6 weeks ( Figure 1a). Water and ethanol mice had similar body weights at the beginning and the end of the 6-week DID treatment (water: 20.5 ± 0.4 g and 24.7 ± 0.3 g; ethanol: 21.0 ±0.4 g and 24.7±0.3 g at week 1 and week 6, respectively; n ¼ 49-65), in agreement with previous results showing ethanol consumption during DID does not affect weight (Lyons et al, 2008).…”
Section: Resultssupporting
confidence: 81%
“…Similarly, DID does not rely on sucrose fading and does not appear to be a result of dietary demand, but does result in physical signs of intoxication. 65,66 Using the DID paradigm, TBI reduced overall intake at 17 days post-injury compared with that of sham controls.…”
Section: Discussionmentioning
confidence: 99%